Evaluation of the interior design of public restrooms in selected malls in Quezon City in terms of the requirements for acessibility, mobility and safety of children - Dizon, Christine Abbey C.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
Using a multiple case study approach, this research made an attempt to evaluate the interior design of public ladies restrooms in selected Quezon City shopping malls in terms of the accessibility, mobility, and safety of children. Likewise, it sought to determine the characteristics and parameters for a child-friendly public restroom through the use of the seven principles of Universal Design and other guidelines pertaining to the accessibility, mobility, and safety of children in the built environment. One representative restroom in each of the four chosen Quezon City malls was picked using purposive sampling. The restrooms were evaluated with the use of site observations, photo documentation, and site measurements. In order to obtain the user's perceptions of the design of restrooms, a survey among mothers with children ages 0 to 12 years old was conducted. Results indicated that significant applications of Universal Design are evident in all four shopping mall restrooms included in this study. The interiors of the restrooms have satisfactory conditions with considerations and provisions for the needs of children and mothers attending to their children. However, there is still room to improve the interior design especially in terms of the room layout and mounting heights of fixtures and features. This may imply a new and existing trend in the local context towards the design of public restrooms, and public spaces in general, that provide adequate accessible features that are in line with the goals of Universal Design. For further research, the study recommends using other approaches such as interviews with mothers, children, and the building managements. A similar study focusing on male restrooms may also be conducted. Furthermore, a comparative study on the existing design of shopping mall restrooms that cater to different target markets based on income groups is recommended.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Restrooms -- Philippines -- Designs and plans; Stores, Retail -- Restrooms -- Philippines